Returning “Home”? Or Dwelling in the Pixel Age: On Invader’s Intermedial Space Invasion - Gaillard, Julie (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2022)
Since 1998, French artist Invader has invaded urban space with mosaics representing pixelated aliens originally imported from the 1978 arcade game Space Invaders. Turning retrogaming into a global artistic project through ever-evolving processes of media combination and intermedial reference, Invader brings together a variety of media and artistic traditions (including mosaics, graffiti, pixel art, arcade games, and a geocaching application) that each involve specific technical and affective inscriptions of humans in space and time. This article shows that the nostalgia mobilized across these distinct medial strata and through their hybridization is not only embraced restoratively but reflectively (Boym, 2001). Nostalgia becomes a vehicle for a voyage across the history of Western dwelling from Antiquity to the techno-capitalist megapolis, a voyage through which the artist seeks to redefine what “dwelling” can mean in a post-digital era.